(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In both English and Uzbek, there is a grammatical category of the number. This category expresses quantitative relations existing in real life, reflected in the consciousness of the speakers of the given language and having a morphological expression in the corresponding forms of the language.